Cancer‐associated fibroblasts in renal cell carcinoma: implication in prognosis and resistance to anti‐angiogenic therapy. (8th August 2021) - Ambrosetti, Damien; Coutts, Michael; Paoli, Charlotte; Durand, Matthieu; Borchiellini, Delphine; Montemagno, Christopher; Rastoin, Olivia; Borderie, Arnaud; Grepin, Renaud; Rioux‐Leclercq, Nathalie; Bernhard, Jean‐Christophe; Pagès, Gilles; et al.
Abstract : Objectives: To investigate the role of cancer‐associated fibroblasts (CAFs) in clear cell renal cell carcinoma (ccRCC) with respect to tumour aggressiveness, metastasis development, and resistance to anti‐angiogenic therapy (vascular endothelial growth factor receptor‐tyrosine kinase inhibitors [VEGFR‐TKI]). Patients and Methods: Our study involved tissue samples from three distinct and independent cohorts of patients with ccRCC. The presence of CAFs and tumour lymphangiogenesis was investigated, respectively, by transcriptional signatures and then correlated with tumour development and prognosis. The effect of these CAFs on tumour cell migration and VEGFR‐TKI resistance was analysed on co‐cultures of ccRCC cells with CAFs. Results: Results from our cohorts and from in silico investigations showed that VEGFR‐TKI significantly increase the number of CAFs in tumours. In the same populations of patients with ccRCC, the proportion of intra‐tumoral CAFs correlated to shorter disease‐free and overall survival. The presence of CAFs was also correlated with lymphangiogenesis and lymph node metastasis. CAFs increased the migration and decreased the VEGFR‐TKI‐dependent cytotoxic effect of tumour cells. Conclusions: Our results show that VEGFR‐TKI promote the development of CAFs, and CAFs favour tumour aggressiveness, metastatic dissemination, and resistance to treatment in ccRCC. CAFs could represent a new therapeutic target to fight resistance to treatment of ccRCC. Targeting CAF and immunotherapies combination are emerging as efficient treatments in many types of solid tumours. Our results highlight their relevance in ccRCC.